Assessing the Level of Scientific Literacy Ability of Fresh Science Education Students in Tertiary Institutions in South-South Nigeria - Owo. W. J; Green. B. (Researchparks Publishing, 2023)
The changing and demanding nature of the world around us requires man to advance his knowledge and skills for him to be able to cope with the changes and demands. This survey study therefore assesses the level of scientific literacy (SL) ability of year one science education students in tertiary institutions in South- South Nigeria using a scientific literacy test (SLT) developed by the researchers based on three competencies (explaining phenomena scientifically, designing and evaluating science investigations, and interpreting data and evidence scientifically). The instrument was administered on a sample of 2,025 students in the 2022/2023 session from selected institutions. Results showed that majority of the students have low ability to design and evaluate investigations, and low ability to interpret data and evidence. However, a good proportion of them show high ability in explaining phenomena and high ability in the overall SL. The results implicitly revealed integrated science (ITS) education students to be better in all the three competencies and the overall SL than their colleagues in biology, chemistry and physics education. It was recommended that science teachers, students and government should play their roles to ensure meaningful science teaching and learning in schools as to help the students gain higher scientific literacy.